Financial Distress Solutions through Improved Financial Performance and GCG with CSR as moderating variable for consumer services companies - Difoasih, Garys; Sihombing, Pardomuan (Jurnal Manajemen, 2023)
The Covid-19 pandemic has reduced Indonesia’s state revenue in the tourism industry. This is caused by government policies that impact companies making it difficult to run their business. As a result, financial performance and corporate governance can be disrupted. This study intends to analyze and determine the power of companies’ financial performance and good corporate governance (GCG) in preventing and overcoming conditions of financial distress in a consumer services company. Based on purposive sampling, the data for this research are 21 consumer services companies listed on the Indonesia Stock Exchange 2019-2021. This study also examines interactions Corporate Social Responsibility (CSR), which is a moderating variable. This research is descriptive with a quantitative explanatory approach, namely a study whose purpose is to explain the relationship between the variables studied and describe them. This research method uses panel regression data analysis. Financial distress in research is measured by Debt Service Coverage (DSCR). Researchers found that liquidity has a positive effect on DSCR, and ownership concentration has a negative effect on DSCR. While profitability, the board size, and gender diversity do not affect DSCR. CSR can strengthen the effect of profitability on DSCR, CSR can weaken the effect of liquidity on DSCR, and CSR can strengthen the effect of ownership concentration on DSCR. This study suggests that the company’s consumer services should focus on financial performance and corporate governance, especially on liquidity and concentration of ownership, to overcome problems of financial distress.